On the measurement of surface diffusivity in disordered nanoporous carbon via molecular dynamics simulations - Mi, Xi; Shi, Yunfeng (Diffusion Fundamentals, 2011)
Gas diffusion in nanoporous carbon includes distinct diffusion modes: surface diffusion on the pore walls and non-surface diffusion away from pore walls. We have performed molecular dynamics (MD) simulations of Ar diffusion in disordered nanoporous carbon. The main objective of this work is to separate the surface diffusion and non-surface diffusion contributions so as to comprehend their respective dependency on the porous structure and testing conditions. The nanoporous carbon sample is obtained using the quenched molecular dynamics (QMD) method. Gas flows are generated by applying a constant external force on each Ar atom, mimicking a constant chemical potential gradient. The contributions from surface diffusion and non-surface diffusion are separated according to the distance of the gas atoms away from the pore wall. We show that the surface diffusivity is affected by the interactions between gas atoms and the pore walls, the temperature, and the loading.